Etude de l’impact de l’incorporation de la Spiruline sur la qualité organoleptique et physicochimique de la Mayonnaise - LAHOUCINE, Halima Amina (My University, 2019)
The objective of this work is to evaluate the impact of incorporating spirulina as an additive on the organoleptic quality of prepared Mayonnaise and to determine its antioxidant and antibacterial properties against two Gram-positive and Gram-negative strains selected for the test. The evaluation of the antioxidant power of the methanol extract of spirulina, carried out by the DPPH free radical scavenging method, showed a good antioxidant efficacy (IC50 = 0.160 mg / ml) and a richness of the polyphenol extract (1, 6 mg EAG / g MS) after quantitative estimation by Folin-Ciocalteu colorimetric method. The results of the antibacterial activity showed an inhibitory effect of spirulina against the two strains tested (E. coli and Staph aureus) with a slightly greater effect against the Staph. aureus strain (18mm in diameter) compared to the E. coli strain (17mm in diameter). The sensory evaluation of our Mayonnaise samples added by Spirulina is not lacking in its color and is still appreciated by the tasters through a questionnaire established in this way. Analysis of the pH and Dornic acidity of our Mayonnaise samples revealed a decreasing pH evolution accompanied by an increasing variation in Dornic acidity. A significant variation in samples with spirulina added to the control sample.
Keywords: Spirulina; Antioxidant potency; Antimicrobial activity; Total polyphenols; Mayonnaise.